2022
DOI: 10.3390/pr10102149
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Streptomyces Species and Validation of Antimicrobial Activity of Their Metabolites through Molecular Docking

Abstract: Finding new antibacterial agents from natural products is urgently necessary to address the growing cases of antibiotic-resistant pathogens. Actinomycetes are regarded as an excellent source of therapeutically important secondary metabolites including antibiotics. However, they have not yet been characterized and explored in great detail for their utility in developing countries such as Nepal. In silico molecular docking in addition to antimicrobial assays have been used to examine the efficacy of chemical sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…in a phylogenetic tree based on the neighborhood-joining method (Figure 1). The Streptomyces S11 isolate demonstrated distinct genetic variance from other species, indicating the likelihood of representing a new Streptomyces species [27,28]. Moreover, MALDI-TOF MS was applied to evaluate the proteome profiles of intact bacterial cells, generating spectra revealing several characteristic peaks, including a discernible one at m/z 5381 in Streptomyces triticirhizae, demonstrating the analysis's credibility up to the genus level with an 8.0 score.…”
Section: Results and Discussion Molecular Characterization Of The Str...mentioning
confidence: 99%
See 1 more Smart Citation
“…in a phylogenetic tree based on the neighborhood-joining method (Figure 1). The Streptomyces S11 isolate demonstrated distinct genetic variance from other species, indicating the likelihood of representing a new Streptomyces species [27,28]. Moreover, MALDI-TOF MS was applied to evaluate the proteome profiles of intact bacterial cells, generating spectra revealing several characteristic peaks, including a discernible one at m/z 5381 in Streptomyces triticirhizae, demonstrating the analysis's credibility up to the genus level with an 8.0 score.…”
Section: Results and Discussion Molecular Characterization Of The Str...mentioning
confidence: 99%
“…Furthermore, 9,12-octadecadienoic acid (Z, Z) exhibits anti-inflammatory, anti-cancer, and anti-arthritic characteristics. This indicates the potential of the metabolite extract in pharmaceutical applications as an antibiotic product [28][29][30][31][32][33][34]. The HR-LCMS system was employed to analyze the metabolite extract of the Streptomyces S11 isolate, identifying a total of 28 components through negative ionization and 29 components through positive ionization.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…The structures were saved in PDBQT format following Kollman charges optimization and polar hydrogen addition using AutoDock software. The antibiotics were downloaded from PubChem in.sdf format, then PyMOL converted them to.pdb format 30 . A 3D affinity grid box near the protein binding sites with a size of 60 × 60 × 60 Å .…”
Section: Methodsmentioning
confidence: 99%
“…The antibiotics were downloaded from PubChem in.sdf format, then PyMOL converted them to.pdb format. 30 A 3D affinity grid box near the protein binding sites with a size of 60 × 60 × 60 Å. It concentrated on the crucial residues in all target proteins where important ligands would bind.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…It also poduces Hygromycin A (HA) that has antibacterial properties due to its capacity to inhibit protein synthesis via a methylenedioxy bridged-aminocyclitol structure. A study report by Bhandari et al [59] identified Streptomyces species, namely S. species_SB1, S. species_SB3, and S. species_SB10, that showed potential antibacterial characteristics in their study on the characterization of antibioticproducing Streptomyces species from untouched habitats in Nepal.…”
Section: Plate 3 Biochemical Tests For Active Actinomycetes Isolatesmentioning
confidence: 99%